Current condition of immune response types - D. A. Sizov; N. Yu. Rukina (Лечащий Врач)
The article discloses a modern definition of the immune response. The phylogenesis of immunity constitutes a single system and is an integral part of the development of multicellular microorganisms. The emergence of multicellular organisms contributed to the formation of a separate community of cells that would be responsible for maintaining homeostasis of the internal environment of the body. The interaction of these cells was a prototype of modern immunity, and the immune response became a form of regulation of the constancy of the internal environment. The role of the immune response in the body is as follows: the search and elimination of foreign particles, both exogenously penetrating (pathogens of infectious diseases) and endogenously formed (cells infected with viruses, tumor cells). The role of the innate and acquired immune response is determined. Particular emphasis is placed on the pathogen recognizing receptors, on their various types. The concept of a pathogen of recognizing receptors is disclosed, their interaction and activation is shown for various types of pathogens. Modern perceptions of interleukins and transcription factors are characterized.